"I am looking to the North for my life"--Sitting Bull, 1876-1881 - Manzione, Joseph, 1957- (University of Utah publications in the American West, 1991)
What happened to the Sioux after the Little Bighorn. Illustrates how two countries, the United States and Canada, struggled to control their potentially explosive common border.